2021
DOI: 10.3389/pore.2021.601693
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Biomarkers Related to Immune Cell Infiltration in Hepatocellular Carcinoma Using Gene Co-Expression Network

Abstract: Hepatocellular carcinoma (HCC) is a common cancer with poor prognosis. Due to the lack of effective biomarkers and its complex immune microenvironment, the effects of current HCC therapies are not ideal. In this study, we used the GSE57957 microarray data from Gene Expression Omnibus database to construct a co-expression network. The weighted gene co-expression network analysis and CIBERSORT algorithm, which quantifies cellular composition of immune cells, were used to identify modules related to immune cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Another study reported that interventional treatment of primary liver cancer can reduce serum HTATIP2/TIP30 and B7-H4 levels, improve liver function and quality of life and prolong the survival times of patients (20). A number of studies reported that SEMA3F, UCK2, NOL10, RAP2A, ZIC2 and SAC3D1 are associated with prognosis and tumour immune infiltration in hepatocellular carcinomas (21)(22)(23)(24)(25). In addition, KIF18A was reported to be associated with tumour immune cell infiltration in adrenocortical carcinomas (26).…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that interventional treatment of primary liver cancer can reduce serum HTATIP2/TIP30 and B7-H4 levels, improve liver function and quality of life and prolong the survival times of patients (20). A number of studies reported that SEMA3F, UCK2, NOL10, RAP2A, ZIC2 and SAC3D1 are associated with prognosis and tumour immune infiltration in hepatocellular carcinomas (21)(22)(23)(24)(25). In addition, KIF18A was reported to be associated with tumour immune cell infiltration in adrenocortical carcinomas (26).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NOP56 is significantly correlated with the survival prognosis, pathological stage, immune infiltration, and tumor progression of patients with hepatocellular carcinoma, and may be used as a target for the diagnosis and treatment of hepatocellular carcinoma in the future. The methylation analysis indicated that the hypomethylation of the NOP56 promoter may lead to the overexpression of NOP56, which proved that expression of NOP56 may be a potential biomarker of hepatocellular carcinoma (66,67). In hepatocellular carcinoma, NOP56 is considered as a potential immune marker associated with HBV virus, which can be processed and presented by antigenpresenting cells (APCs) to induce immune responses.…”
Section: Nop56 and Hepatocellular Carcinomamentioning
confidence: 99%